2015
DOI: 10.1039/c4nr07458k
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ceria nanofilms from structure prediction

Abstract: Experimentally, Ce2O3 films are used to study cerium oxide in its fully or partially reduced state, as present in many applications. We have explored the space of low energy Ce2O3 nanofilms using structure prediction and density functional calculations, yielding more than 30 distinct nanofilm structures. First, our results help to rationalize the roles of thermodynamics and kinetics in the preparation of reduced ceria nanofilms with different bulk crystalline structures (e.g. A-type or bixbyite) depending on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
(60 reference statements)
2
12
0
Order By: Relevance
“…At specific concentrations of Ce 3+ sites different structural phases are expected to be stable in the bulk material 27,28 . In ultrathin films the situation is even more complex, due to the possible stabilization of low dimensionality substrate-induced metastable phases 12,[29][30][31][32] . When Pt is used as a substrate, previous studies by our group showed the formation of peculiar reconstructions in the LEED patterns of ultrathin films at significant degrees of reduction, indicating important rearrangements of the surface structure 13,14 .…”
Section: Resultsmentioning
confidence: 99%
“…At specific concentrations of Ce 3+ sites different structural phases are expected to be stable in the bulk material 27,28 . In ultrathin films the situation is even more complex, due to the possible stabilization of low dimensionality substrate-induced metastable phases 12,[29][30][31][32] . When Pt is used as a substrate, previous studies by our group showed the formation of peculiar reconstructions in the LEED patterns of ultrathin films at significant degrees of reduction, indicating important rearrangements of the surface structure 13,14 .…”
Section: Resultsmentioning
confidence: 99%
“…The different phases stabilized in reduced cerium oxide films at reduced dimensionality have also been addressed by theoretical studies employing the simulated mechanical annealing approach to select the most stable structures, which were subsequently simulated by DFT [50]. The study shows that the relative stability of the C-type and A-type phases in ultrathin films depends on the in-plane lattice parameter [50].…”
Section: Reduced Cerium Oxide Epitaxial Filmsmentioning
confidence: 99%
“…The study shows that the relative stability of the C-type and A-type phases in ultrathin films depends on the in-plane lattice parameter [50]. Furthermore, it identifies a new structure without a bulk counterpart which is more stable than the A-type and C-type phases at larger in-plane lattice parameters, such as those that might be induced by epitaxy on Re(0001) or Pt(111) [50]. This and related studies provide important input to unravel the origin of the complex phases identified experimentally and to understand their properties.…”
Section: Reduced Cerium Oxide Epitaxial Filmsmentioning
confidence: 99%
“…The exposed works show that ultrathin cerium oxide films offer new opportunities in view of obtaining modifications of the material properties, and in particular for the stabilization of metastable structural phases. This last issue has been investigated also in a rather recent theoretical investigation aimed at identifying the most stable Ce 2 O 3 structures at the ultrathin limit [56]. The work, using simulated mechanical annealing searches and DFT calculations, shows that different ultrathin film structures are stable at different values of the in plane lattice parameter and it identifies in particular a new structure, which does not correspond to any known bulk crystalline polymorph, which is more stable than the A-type and than the c-type Ce 2 O 3 structures at specific, relatively large, in-plane lattice parameters (figure 5) [56].…”
Section: Cerium Oxide Two-dimensional Filmsmentioning
confidence: 99%
“…This last issue has been investigated also in a rather recent theoretical investigation aimed at identifying the most stable Ce 2 O 3 structures at the ultrathin limit [56]. The work, using simulated mechanical annealing searches and DFT calculations, shows that different ultrathin film structures are stable at different values of the in plane lattice parameter and it identifies in particular a new structure, which does not correspond to any known bulk crystalline polymorph, which is more stable than the A-type and than the c-type Ce 2 O 3 structures at specific, relatively large, in-plane lattice parameters (figure 5) [56]. As mentioned at the beginning of this section, a few studies have also been focused on the stabilization of ultrathin cerium oxide films exposing surfaces different from the (111) on metal substrates.…”
Section: Cerium Oxide Two-dimensional Filmsmentioning
confidence: 99%